Pengembangan Pelatihan Bagi Sumberdaya Manusia Koperasi Agroindustri (Universitas Esa Unggul, 2012)
AbstractDekopin is the apex of Indonesian Cooperative Movement. Dekopin has responsibility to develop the cooperatives human resources and business of cooperatives. Cooperatives have to be ready to face environmental change on business, politics and laws. To anticipate that, cooperative movement has to develop and increase the skill of cooperative human resources. DEKOPIN has responsibility to conduct the training to increase the skill of cooperative members. The objective of this study is to develop the education and training for human resources of agroindustrial-based cooperatives that are suitable for competitiveness in globalization era. This study uses the Analitycal Hierarchy Process (AHP) to collect the competency that‘s needed by cooperative’s human resources and Training Need Assessment Tools (T-NAT) for setting of the training curriculum. The result of the study indicates that the training curriculum should be arranged on the discrepancy based of competency at this time.Kata kunci: pemberdayaan, koperasi, AHP